Nation and National Identity in the Hebrew Bible and Ancient Israel? Engaging the Approaches of Jacob Wright and Mei Hualong - Krause, Joachim J. 1978- (2025)
“Nation,” “national identity” and related terms appear repeatedly in recent exegetical works on the Hebrew Bible and ancient Israel. Two examples, the monographs War, Memory, and National Identity in the Hebrew Bible by Jacob Wright (Cambridge: Cambridge University Press, 2020; pp. xii + 283) and Nation and Empire as Two Trends of Political Organization in the Iron Age Levant by Mei Hualong (Leiden: Brill, 2024; pp. xvi + 495), are reviewed here against the background of research on the socio-political structure of Iron Age territorial kingdoms of the southern Levant. The present article argues that, in a historical perspective, this research places us in a better position to consider the ways in which ancient Israel and Judah were different from a modern nation. However, the current resurgence of the term “nation” raises the question as to why ancient Israel and its representation in the Hebrew Bible prove so attractive for those who inquire into the origins of the idea of a nation.
Keywords: Nation; National Identity; Empire; war commemoration; Literaturbericht